2014
DOI: 10.1371/journal.pone.0088171
|View full text |Cite
|
Sign up to set email alerts
|

Bar Represses dPax2 and Decapentaplegic to Regulate Cell Fate and Morphogenetic Cell Death in Drosophila Eye

Abstract: The coordinated regulation of cell fate and cell survival is crucial for normal pattern formation in developing organisms. In Drosophila compound eye development, crystalline arrays of hexagonal ommatidia are established by precise assembly of diverse cell types, including the photoreceptor cells, cone cells and interommatidial (IOM) pigment cells. The molecular basis for controlling the number of cone and IOM pigment cells during ommatidial pattern formation is not well understood. Here we present evidence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
(40 reference statements)
0
9
0
1
Order By: Relevance
“…Additionally we observed enrichment of ‘MAP kinase activity’ (GO:0004709, p = 0.00109) in genes downregulated within Alba wings. In Drosophila , BarH-1 represses Decapentaplegic, a morphogen that is homolog to TGFβ 38 . TGFβ can activate signalling cascades, including MAP kinase pathways 39 .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally we observed enrichment of ‘MAP kinase activity’ (GO:0004709, p = 0.00109) in genes downregulated within Alba wings. In Drosophila , BarH-1 represses Decapentaplegic, a morphogen that is homolog to TGFβ 38 . TGFβ can activate signalling cascades, including MAP kinase pathways 39 .…”
Section: Resultsmentioning
confidence: 99%
“…Although Ance null mutants do not exhibit obvious developmental defects, it is important to note that loss of Ance can modulate the phenotypes of impaired Dpp signaling. It has been shown that overexpression of dpp by GMR - Gal4 causes severe roughness and bulging of the adult eye 46 . We showed that reduced Ance partially suppressed the effects of Dpp overexpression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, the sgRNAs for dpp4, dpp5, engrailed, hairy, hid1, hid2, rad51, reaper2 increased the expression of their target genes at more moderate levels ( Figure 2B). The sgRNAs dpp1, dpp2, dpp3 and reaper2 were found to suppress gene expression compared to contols, possibly due to binding competition and steric-hindrance with cis-regulatory factors at the site of tran-scription (dpp 30 and reaper 31,32 are both known to play a developmental role in wild-type eyes). Subtle increases in the expression of developmental genes induced through dCas9-VPR are known to have pronounced developmental phenotypes when expressed in Drosophila tissues 23 .…”
Section: Dcas9 Transactivation By Sgrnas In the Drosophila Eyementioning
confidence: 99%